Effect of Parasitic Elements on the Performance of Buck-Boost Converter for PV Systems - Subramanya x Bhat; Nagaraja H N (International Journal of Electrical and Computer Engineering (IJECE), 2014)
In the proposed study, MOSFET device used in buck-boost converter for PV systems is studied. The parameter of MOSFET Rds(on) is varied and its effect on output voltage is studied. The parasitic elements in inductor and capacitor such as resistance on buck-boost converter performance are studied.  From the proposed study it has been found that the effect of parasitic resistance in capacitor is less as compared to parasitic resistance effect of inductor. Also the proposed study gives better insight into parasitic effect of Printed Circuit Board and losses incurred due to the same. In PV systems buck-boost converter is used to convert solar energy to electrical energy which is then stored in battery to drive the loads. These parasitic elements will have considerable effect on the performance of buck-boost converter such as efficiency and output voltage as validated by experimental results.DOI:http://dx.doi.org/10.11591/ijece.v4i6.6855